(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2022)
Ayurveda is one of the oldest healing sciences with a vast number of medicines for curing diseases and for protecting the healthiness of healthy people. Relevant medicines possess potent Jwaraghna, Rasayana, etc. pharmacological activities. Hitherto, antimicrobial activity is given less attention. Nevertheless, microbes were synonymously referred as “Yathudana”, “Rakshasa”, “Pishacha”, “Asura”, “Gandharva” and “Krimi” in Samhita. These terms resulted in this research to study the antimicrobial activity of some commonly used Ayurveda medicines. A total of thirteen Ayurveda medicines, including Churna, Arishta, Avaleha, Vati and Rasaushadha, were tested for antimicrobial activity by using agar well diffusion method and by disc diffusion method under strict aseptic conditions and following standard laboratory guidelines. The findings of this study were very encouraging as all 13 Ayurveda medicines exhibited potent antimicrobial activity in general. Rasamanikya and Shwasakuthara rasa were shown to be effective against Staphylococcus aureus. Chyawana prashavalehaya and Chandraprabha vati exhibited antimicrobial activity against Escherichia coli. Sudarshana and Thrikatu churna were found to have the strongest antimicrobial activity against S. aureus and E. coli. Amrtarishta was effective in eradicating Staphylococcus aureus, Escherichia coli and Salmonella typhi. Draksharishtaya was found to have antimicrobial activity against Staphylococcus aureus, Escherichia coli, Salmonella typhi and Bacillus subtilis, Dashamularishtaya was effective against Shigella flexneri, Aspergillus niger and Pseudomonas auriginosa. Only Thalisadi churna exhibited antifungal activity against Candida albicans. Exhibit results clearly established the potent antimicrobial activity of all thirteen Ayurveda medicines against common human pathogens and might offer new hopes for controlling infectious diseases and preventing the emergence of resistant variants.